Analysis of solar energy technology in leading countries - Kaliappan, Kannan; Sankar, M; Karthikeyan, B; Vineeth, Budamkayala; Raju, V. Chetan (Institute of Advanced Engineering and Science, 2019)
In the present generation energy plays a vital role in our world and for human life it´s very important factor. There is a methodical meeting taking place regarding the conservation of energy and every time there is a review in the agenda. Energy demand and supply were endeavored by these countries. To rectify these problems, there should be more research in the generation of energy with the greater efficiency and try to use energy in more efficient manner. Solar energy remains as the most prominent source of energy as it is cost effective and environmentally friendly. Reviews convey that solar energy systems will play a major role in the power generations. As per present scenario there is a great importance to the solar energy using photovoltaic systems. Photovoltaic systems exhibit an important role for solar energy production.